Physical and geographical analysis of current state of Otrar district with using geoinformation technology (Journal of Geography and Environmental Management, 2023)
Otrar district is an agrarian district located in the south part of the Kazakhstan, on natural-territorial  complexes of which from ancient times been exposed anthropogenic factors. Based on the latest data, due to the intensity of natural and anthropogenic factors, a significant transformation of natural and territorial complexes as a whole and of its individual components is observed in the object of research. And the existing old cartographic data does not fully reflect the current state. In this regard, in order to analyze the physical and geographical state and to identify trends and specifics of transformation of the geosystems of the Otrar district, physical and geographical studies were carried out on the basis of GIS technologies: Arcgis 10.4 and Ilwis 3.4. The geographic database of the research area was created, after digitizing the raster topographic maps. In the course of the study, the tendency of transformation of geosystems of the object was revealed and their comparative analysis was carried out by deciphering space images of the satellite Landsat 8OLI. For this purpose, advanced methods and principles of foreign and domestic scientists on the application of GIS. As a result, for the first time at a scale of 1: 200,000, a physical geographical map of the Otrar district was compiled, which describes the main specific characteristics of the physical geographical peculiarity of the territory. Also, focusing on the latest publications, the degree, cause-effect relationships of occurrence and impact of anthropogenic factors on geosystems are analyzed.The results of the study can be applied by specialists of the district administration of agriculture and environmental institutions to solve the problems of planning and design in the agricultural structure.
Keywords: Otrar district, methods of construct a physical-geographical map, delta of the Syrdarya river, anthropogenic transformation of geosystems, GIS technology, deciphering space images.